Kinship in the novel limpapeh as a post-reformation Minangkabau local color literature - Zulfitriyani; Nuruddin; Zainal Rafli (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to gain knowledge and discoveries about kinship in Minangkabau local color novels represented by AR Rizal's Limpapeh novel. The author's social background indirectly influences this. Concerning kinship is worth researching because, since the time of modern literature in Indonesia, Minangkabau literature was formerly famous for its ironic tales related to marriage and customs. Meanwhile, through his novel, AR Rizal shows the condition of today's society with a kinship order that still maintains the past system, and it turns out that it is still often found in the reality of today's society even though this is only expressed in the form of works of fiction. This qualitative research uses the content analysis method, namely research that discusses information in depth and then marks it in the form of quotations in the novel as data marked in the text. The results of this study found that the form of kinship in the novel Limpapeh by AR Rizal is in the form of suku and sako, mamak and kemenakan, bako and anak pisang, andan and pasumandan. In terms of kinship, it shows that ethnic issues and the role of Mamak are still essential and are used today in Minangkabau society. This indirectly shows that mimetic elements in fictional literary works can still be found in society.